Isra Hayati Pengaruh Akuntabilitas dan Transparansi Terhadap Kepercayaan Muzakki pada Lembaga Pengelolaan Zakat dengan Literasi Zakat Sebagai Variabel Intervening pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Langkat - Isra Hayati; Irfan; Widia Astuty (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research is to test and analyze the influence of accountability and transparency on muzakki trust mediated by delicious literacy. The approach used in this research is an associative approach. The population in this study were muzakki who fulfilled their obligations in paying zakat to the Langkat Regency National Zakat Amil Agency (BAZNAS). The sample in this study used a saturated sample, making all members of the population the sample so that the number of respondents was 99 people. Data collection techniques in this research used documentation studies and questionnaires. The data analysis technique in this research uses a quantitative approach using statistical analysis using Auter Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that accountability has no effect on muzakki's trust, transparency and zakat literacy have a significant effect on muzakki's trust, then accountability and transparency have a significant effect on zakat literacy, and zakat literacy mediates the influence of accountability and transparency on muzakki's trust at the National Zakat Amil Agency Zakat Management Institution ( BAZNAS) Langkat Regency